Certification of Persons: Empirical study in the field of energy construction in Latvia - Maija Kavosa; Inga Lapiņa; Kārlis Briņķis (Cogent Business & Management, 2017)
The development of the energy sector is an essential precondition for a sustainable growth of the national economy; therefore, the national energy policy is directed not only to the promotion of competition and efficient use of energy resources, but also to an increased security of power supply. Due to the fact that faulty operation of electrical equipment and construction or maintenance of low-quality dangerous electrical equipment may cause serious risks, there is a need for professional qualification certificate stating the person's competence in the sphere. The aim of the study is to analyse the certification process of energy constructors and evaluate the compliance of competence assessment and implementation of supervision of the constructors' independent practice with the requirements laid down in the sphere of electric power in order to develop possible solutions for the improvement of the certification process of energy constructors. The authors' study allows assessing the certification process of energy constructors from the customers' point of view, i.e. finding out what is important to the certified construction specialists, not to the certification bodies or supervisory authorities. The results of the evaluation show that the construction specialists' requirements for the certification service performance are not fully met and there exist some challenges to be solved to ensure the professional competence of persons to be certified with the requirements laid down in the particular industry.
Keywords: 650